2010
DOI: 10.1007/s00192-010-1162-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical botulinum toxin A injections in the treatment of painful bladder syndrome/interstitial cystitis: a systematic review

Abstract: Hypothesis / aims of study The aim of our systematic review was to assess the effectiveness and adverse effects of intravesical (BTX-A) in painful bladder syndrome (PBS) or interstitial cystitis (IC).Study design, materials and methods Randomised controlled trials (RCTs) and prospective studies of relevance were identified, assessed for inclusion, then analyzed by two independent reviewers. Newcastle Ottawa scale and Jadad scale were used to assess the qualities of included prospective nonrandomized and RCTs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Recently, intravesical injection of BoNT-A has been introduced as a new treatment modality. 2 Repeated injections of BoNT-A are known to provide better therapeutic effects and long-term success rates than a single injection. 3 However, the efficacy of this treatment is still controversial, partly because of a limited number of RCT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intravesical injection of BoNT-A has been introduced as a new treatment modality. 2 Repeated injections of BoNT-A are known to provide better therapeutic effects and long-term success rates than a single injection. 3 However, the efficacy of this treatment is still controversial, partly because of a limited number of RCT.…”
Section: Introductionmentioning
confidence: 99%
“…Tirumuru et al suggested that BoNTA might show a trend toward short-term benefit on urodynamic parameters based on RCTs [6]. Giannantoni et al proposed a comprehensive IC/PBS treatment strategy, such as oral medication, intravesical instillations, and combined treatment, but the results obtained had high heterogeneity, with uncertain conclusions [14].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous treatments for IC/PBS, including diet therapy, behavior adjustment training (BAT), oral medication, intravesical instillation, and surgical intervention [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have additionally shown an anti-inflammatory effect and reduction of substance P in the urine following intradetrusor BTX-A injection. 19,20 Sacral nerve stimulation (SNS) is not widely available. It involves placing a lead into sacral foramen S3, connected to an implantable neurostimulator under the skin just above the sacrum.…”
Section: Surgical Optionsmentioning
confidence: 99%